Indian Democracy and Contemporary Challenges: An Assessment through the Lens of Dr. B.R. Ambedkar - Suresh Takatarao, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
This analytical research paper assesses the contemporary challenges facing Indian democracy, utilising the critical framework established by Dr B.R. Ambedkar, the father of the Indian Constitution. The study specifically evaluates the impact of recent political issues, including executive overreach, institutional erosion, and rising socio-economic polarisation, against Ambedkar’s three core warnings: the necessity of achieving social democracy, the danger of hero-worship in politics, and the abandonment of the ‘Grammar of Anarchy.’ Findings suggest that India’s established democracy is under considerable strain. The accumulation of political power has systematically compromised constitutional institutions, leading to legislative complacency and strategic judicial retreat. Simultaneously, the failure to address entrenched socio-economic inequalities and the rise of institutionalised majoritarianism have undermined the requisite foundation of social democracy and fraternity.
Keywords: Democracy; Contemporary politics; Dr. B.R. Ambedkar; Democratic Survival